A Geologically Based Indoor‐Radon Potential Map of Kentucky. (23rd November 2020) - Haneberg, William C.; Wiggins, Amanda; Curl, Douglas C.; Greb, Stephen F.; Andrews, William M.; Rademacher, Kathy; Rayens, Mary Kay; Hahn, Ellen J.
Abstract: We combined 71, 930 short‐term (median duration 4 days) home radon test results with 1:24, 000‐scale bedrock geologic map coverage of Kentucky to produce a statewide geologically based indoor‐radon potential map. The test results were positively skewed with a mean of 266 Bq/m 3, median of 122 Bq/m 3, and 75th percentile of 289 Bq/m 3 . We identified 106 formations with ≥10 test results. Analysis of results from 20 predominantly monolithologic formations showed indoor‐radon concentrations to be positively skewed on a formation‐by‐formation basis, with a proportional relationship between sample means and standard deviations. Limestone (median 170 Bq/m 3 ) and dolostone (median 130 Bq/m 3 ) tended to have higher indoor‐radon concentrations than siltstones and sandstones (median 67 Bq/m 3 ) or unlithified surficial deposits (median 63 Bq/m 3 ). Individual shales had median values ranging from 67 to 189 Bq/m 3 ; the median value for all shale values was 85 Bq/m 3 . Percentages of values falling above the U.S. Environmental Protection Agency (EPA) action level of 148 Bq/m 3 were sandstone and siltstone: 24%, unlithified clastic: 21%, dolostone: 46%, limestone: 55%, and shale: 34%. Mississippian limestones, Ordovician limestones, and Devonian black shales had the highest indoor‐radon potential values in Kentucky. Indoor‐radon test mean values for the selected formations were also weakly, but statistically significantly, correlated with mean aeroradiometric uranium concentrations. To produce a map useful to nonspecialists, we classified each of the 106 formations into five radon‐geologic classes on the basis of their 75th percentile radon concentrations. The statewide map is freely available through an interactive internet map service. Plain Language Summary: Exposure to high levels of radon is the second leading cause of lung cancer in the United States and greatly increases the likelihood of lung cancer in people who are also exposed to tobacco smoke. Produced by the radioactive decay of naturally occurring uranium in rocks, radon gas migrates into homes where it and its radioactive decay products can be inhaled by humans. We know that different kinds of bedrock produce different amounts of radon. To illustrate the danger posed by indoor radon in Kentucky, we combined results from 71, 930 radon home test kits with geologic maps showing different kinds of bedrock and produced a geologically based and highly interactive indoor‐radon potential map of Kentucky. Our map is available as a web‐based interactive service hosted by the Kentucky Geological Survey and requires only a desktop or mobile web browser to use. The map also includes links to supplemental information that users can access to better understand the indoor‐radon danger in their counties, encourage them to have their homes tested, and, if appropriate, mitigate the problem. Key Points: Bedrock geologic units in Kentucky have lithologically controlled indoor‐radon potential Carbonate sedimentary rocks generally have higher indoor‐radon potential than nonshale clastic sediments and sedimentary rocks We used geologic map coverage and radon test results to produce an interactive statewide indoor‐radon potential map for nonspecialists